2020
DOI: 10.1039/c9fo00881k
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin ameliorates diabetic neuropathic pain by modulation of oxidative-nitrosative stress, cytokines and MMP-9 levels

Abstract: Diabetes mellitus is a serious debilitating epidemic affecting all social strata, imposing huge health, social and economic burdens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…Evidence-Based Complementary and Alternative Medicine inflammatory, antioxidant, and neuroprotective effects that could improve neuropathic pain, neuronal damage, and injury [119,303,304]. Glycyrrhizin and naringenin reduce inflammatory and neuropathic pain-like behaviors by modulating the secretion of inflammation-associated cytokines and mediators, as well as the activities of cyclic guanosine monophosphate (cGMP) and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) signalings [120,301,[305][306][307][308][309][310][311][312][313][314]. Isoliquiritigenin was reported to possess analgesic, antispasmodic, and relaxant properties [315,316].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence-Based Complementary and Alternative Medicine inflammatory, antioxidant, and neuroprotective effects that could improve neuropathic pain, neuronal damage, and injury [119,303,304]. Glycyrrhizin and naringenin reduce inflammatory and neuropathic pain-like behaviors by modulating the secretion of inflammation-associated cytokines and mediators, as well as the activities of cyclic guanosine monophosphate (cGMP) and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) signalings [120,301,[305][306][307][308][309][310][311][312][313][314]. Isoliquiritigenin was reported to possess analgesic, antispasmodic, and relaxant properties [315,316].…”
Section: Discussionmentioning
confidence: 99%
“…Baicalein and naringenin ameliorate diabetic nephropathy by mitigating renal oxidative stress, normalizing serum pro-inflammatory cytokines levels, improving structural changes in renal tissues, and reducing apoptosis [120][121][122][123]. Besides, naringenin might also ameliorate diabetic vascular dysfunction, diabetic neuropathy, and diabetic retinopathy [124][125][126].…”
Section: Flavonoidsmentioning
confidence: 99%
“…Besides, there was currently no effective treatment to control oxaliplatin-induced NP optimally. Previous reports indicated that flavonoids could prevent the occurrence and development of chemotherapy-induced NP via suppressing apoptosis, oxidative stress, astrocyte and microglial activation, and inflammatory responses (Zhang Singh et al 2020;Xie et al 2020;Siddiqui et al 2021). Therefore, flavonoids may be a novel analgesic drug in the prevention and treatment of chemotherapy-induced NP.…”
Section: Discussionmentioning
confidence: 99%